Performance of porous coated 5 × 3 staggered horizontal tube bundle under flow boiling. (5th January 2018) - Swain, Abhilas; Das, Mihir Kumar
Highlights: Flow boiling on outside porous coated tube bundles is studied. A new type of correlation is proposed in terms of Peclet number and Froud Number. ANFIS model is also developed and is found to be performing better than empirical model. Variation of HTC with mass flux is found to be insignificant up to a certain value and then it decreases. Abstract: The present article focuses on the flow boiling heat transfer performance of plasma sprayed copper coated tube bundles. The details of the flow boiling experiments over coated tube bundles is presented in the article. The variations of bundle average heat transfer coefficients are presented and analysed for saturated flow boiling of distilled water with respect to operating parameters such as heat flux, mass flux and pitch to diameter ratio. The range of operating parameters considered for present investigation is as follows: heat flux = 12.25–65.94 kW/m 2, mass flux = 20.25–192.9 kg/m 2  s and pitch to diameter ratio = 1.25, 1.6 and 1.95. The results show that the bundle averaged heat transfer coefficient increases with the increase in heat flux. However, it does not vary significantly with mass flux up to a certain value and decreases thereafter with further increase in mass flux. The tube bundle with lower pitch to diameter ratio is observed to be performing better. Semi-empirical correlation and ANFIS model are developed to predict the flow boiling bundle average heat transfer coefficients.